Application of Da Vinci Robot and Thoracoscopy in Radical Lung Cancer Surgery. (16th March 2022) - Qi, Fenqiang; Xiang, Minfeng; Deng, Yuxin; Huang, Wei; Sun, Yan
Abstract : In this article, we have explored the feasibility and safety of Da Vinci's robotic surgery system in the radical resection of lung cancer. For this purpose, 73 cases of patients with lung cancer who underwent radical resection in the thoracic surgery of our hospital, particularly from July to September 2020, were collected, of which 22 cases operated with the Da Vinci robot were the Da Vinci robot group, including 11 men and 11 women. The 51 patients who underwent thoracoscopic surgery were in the thoracoscopic group, including 24 males and 27 females. All 22 patients in the Da Vinci robot group completed the operation under the Da Vinci robot operation system without conversion to thoracotomy. In the thoracoscopic group, 49 patients successfully completed the operation under thoracoscopy, and 2 patients were converted to thoracotomy. There was a significant difference between the two groups in the average operation time and the number of lymph nodes, but there was no significant difference in the amount of intraoperative bleeding and postoperative hospital stay. Compared with thoracoscopic radical lung cancer surgery, Da Vinci's robotic surgery system is equally safe and effective, and more lymph nodes are cleaned during surgery.